Mutant p53 murine oviductal epithelial cells induce progression of high-grade serous carcinoma and are most sensitive to simvastatin therapy in vitro and in vivo - Madison Pereira; Alice Glogova; Jacob Haagsma; Julia Stewart; Trevor G. Shepherd; Jim Petrik (BMC, 2023)
Abstract High-grade serous carcinoma (HGSC) is the most common and aggressive subtype of epithelial ovarian cancer, characterized by gain-of-function TP53 mutations originating in the fallopian tube epithelium. Therapeutic intervention occurs at advanced metastatic disease, due to challenges in early-stage diagnosis, with common disease recurrence and therapy resistance despite initial therapy success. The mevalonate pathway is exploited by many cancers and is potently inhibited by statin drugs. Statins have shown anti-cancer activity in many, but not all cancers. Here, we investigated the role of p53 status in relation to mevalonate pathway signaling in murine oviductal epithelial (OVE) cells and identified OVE cell sensitivity to statin inhibition. We found that p53R175H mutant and Trp53 knockout OVE cells have increased mevalonate pathway signaling compared to p53 wild-type OVE cells. Through orthotopic implantation to replicate the fallopian tube origin of HGSC, p53R175H mutant cells upregulated the mevalonate pathway to drive progression to advanced-stage ovarian cancer, and simvastatin treatment abrogated this effect. Additionally, simvastatin was more efficacious at inhibiting cell metabolic activity in OVE cells than atorvastatin, rosuvastatin and pravastatin. In vitro, simvastatin demonstrated potent effects on cell proliferation, apoptosis, invasion and migration in OVE cells regardless of p53 status. In vivo, simvastatin induced ovarian cancer disease regression through decreased primary ovarian tumor weight and increased apoptosis. Simvastatin also significantly increased cytoplasmic localization of HMG-CoA reductase in ovarian tumors. Downstream of the mevalonate pathway, simvastatin had no effect on YAP or small GTPase activity. This study suggests that simvastatin can induce anti-tumor effects and could be an important inhibitor of ovarian cancer progression.